Designing with objects: object-oriented design patterns explained with stories from Harry Potter - Kak, Avinash C (Wiley, 2014)
Here is a book that takes the sting out of learning object-oriented design patterns! Using vignettes from the fictional world of Harry Potter, author Avinash C. Kak provides a refreshing alternative to the typically abstract and dry object-oriented design literature. Designing with Objects is unique. It explains design patterns using the short-story medium instead of sterile examples. It is the third volume in a trilogy by Avinash C. Kak, following Programming with Objects (Wiley, 2003) and Scripting with Objects (Wiley, 2008). Designing with Objects confronts how difficult it is for students to learn complex patterns based on conventional scenarios that they may not be able to relate to. In contrast, it shows that stories from the fictional world of Harry Potter provide highly relatable and engaging models. After explaining core notions in a pattern and its typical use in real-world applications, each chapter shows how a pattern can be mapped to a Harry Potter story. The next step is an explanation of the pattern through its Java implementation. The following patterns appear in three sections: Abstract Factory, Builder, Factory Method, Prototype, and Singleton; Adapter, Bridge, Composite, Decorator, Facade, Flyweight, and Proxy; and the Chain of Responsibility, Command, Interpreter, Iterator, Mediator, Memento, Observer, State, Strategy, Template Method, and Visitor. For readers’ use, Java code for each pattern is included in the book’s companion website. ● All code examples in the book are available for download on a companion website with resources for readers and instructors. ● A refreshing alternative to the abstract and dry explanations of the object-oriented design patterns in much of the existing literature on the subject. ● In 24 chapters, Designing with Objects explains well-known design patterns by relating them to stories from the fictional Harry Potter series